Governance of the National Development Planning and Budgeting Synchronization Network - Irma Sakty; M. Thahir Haning; Nurdin Nara; Syahribulan Syahribulan (Journal La Sociale, 2023)
Development is a human activity that has complex problem dimensions, continues to change dynamically and contains wide differences in substance. Every country in carrying out the development process requires a set of values or goals to be achieved as a reflection or representative of the common interests/decisions of its people. The aim of the research is to find out how appropriate national development planning and budgeting synchronization network governance is in Indonesia. This research will use a post-positivism research approach and use qualitative methods. Research location at the center (Bappenas, Ministry of Finance, Ministry of Home Affairs), representatives of Regional Government actors and other agencies/institutions in the regions involved such as representatives of BPK/BPKP DPR/DPRD, Community Organizations/Academics). The resources possessed in the national development planning and budgeting synchronization network can be concluded that the main resources that play an important role in the network are: (1) the availability of professional planning human resources; (2) budget availability to manage planning programs/activities.